Utilizing Information and Communication Technology in Scalable Management Strategies for Teacher Development - Rukajat, Ajat; Gusniar, Iwan Nugraha; Abas, Totoh Tauhidin; Nurkhalizah, Ervin; Bachruddin, Rizal (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Teachers are human resources who play an important and strategic role in the success of learning so they must fulfill adequate competencies. Teachers with low competence will not be able to produce students who excel both academically and non-academically. Efforts to improve teacher competency include education and training. OBJECTIVE: This research aims to see how information and communication technology is used in developing teachers’ pedagogical and professional competencies. METHODS: This research was carried out using a descriptive qualitative approach. The data used in this research was obtained from various relevant sources. RESULTS: The results of this research found that increasing teacher pedagogical and professional competence through the integration of Information and Communication Technology (ICT) and scalable management strategies opens up new perspectives on the importance of investing in the development of teaching staff. CONCLUSION: The alignment of modern pedagogical approaches with the use of technology and efficient management strategies allows teachers to develop as more effective and competitive educators. Increasing pedagogical competence allows educators to create more dynamic and relevant learning environments for students. By incorporating innovative teaching methods, such as the use of digital tools and resources, teachers can adapt learning to students’ diverse learning styles.